ANALYSIS OF THE HEALTH LEVEL OF BANK NTB SYARIAH USING THE RGEC METHOD FOR THE 2020–2024 PERIOD - Evrita Putri Azzahroh; Nur Fazila Milawati (Jurnal Dinamika Ekonomi Syariah, 2026)
This study aims to analyze the health level of Bank NTB Syariah during the 2020–2024 period using the RGEC method, which comprises Risk Profile, Good Corporate Governance (GCG), Earnings, and Capital, as stipulated by the Financial Services Authority (OJK). The research employs a descriptive quantitative approach using secondary data obtained from the bank’s published annual financial reports. The results indicate that Bank NTB Syariah demonstrates a generally healthy financial condition throughout the observation period. From the Risk Profile aspect, the Non-Performing Financing (NPF) ratio consistently remains below the regulatory threshold of 5%, reflecting effective credit risk management, while the Financing to Deposit Ratio (FDR) shows the bank’s adequate liquidity management despite fluctuations in third-party funds. In terms of Good Corporate Governance, qualitative analysis based on annual reports and shareholders’ meetings indicates that governance practices are implemented in accordance with OJK guidelines and fall within the healthy category. The Earnings component, measured through Return on Assets (ROA), Return on Equity (ROE), and BOPO, reveals stable profitability performance, accompanied by a gradual improvement in operational efficiency. Meanwhile, the Capital aspect demonstrates strong capital adequacy, indicating the bank’s ability to absorb potential risks and support sustainable growth. Overall, the RGEC assessment confirms that Bank NTB Syariah has maintained sound financial performance and risk management following its conversion into a fully Sharia-compliant regional bank